How do people experience innocent suffering? - Smirnov, Evgeny (Frontiers in Psychology, 2023)
The paper examines the psychological facet of innocent suffering. One can find a description of this phenomenon in social psychology as a factor that affects the belief in a just world, but there is a lack of qualitative scientific data about related psychological features, processes, copings, and consequences on the personality level. To study innocent suffering, a semi-structured in-depth interview was conducted (31 respondents, ~223 minutes per respondent, 6924 minutes in total) aimed to gather data about the experiences of innocent sufferings happened to participants. For the analysis of texts, a narrative and content analysis are used within the framework of grounded theory. The reliability of the results is based on expert assessment. As a result, six essential properties of innocent sufferings were identified: complexity, stability, distress, injustice, casual incoherence, and breaks of integrity of a life story. The most 'popular' life domains, in which participants reported about innocent sufferings, are violence, abuse (physical and psychological), and quitting romantic relationships. It is proposed a scientific definition of innocent suffering and the prototype of the phenomenon.